'You`re the best liar in the world`: a grounded theory study of rowing athletes` experience of low back pain - Wilson, F.; Ng, L.; O'Sullivan, K.; Caneiro, J. P.; O'Sullivan, P. P. B.; Horgan, A.; Thornton, J. S.; Wilkie, K.; Timonen, V. (British Journal of Sports Medicine, 2021)
Objectives: Low back pain (LBP) is common in rowers and leads to considerable disability and even retirement. The athlete voice can help clinicians to better understand sport-related pain disorders. We aimed to capture the lived experience of LBP in rowers.